Do Thirty-Second Post-activation Potentiation Exercises Improve the 50-m Freestyle Sprint Performance in Adolescent Swimmers? - Abbes, Zied; Chamari, Karim; Mujika, Iñigo; Tabben, Montassar; Bibi, Khalid W.; Hussein, Ali Mostafa; Martin, Cyril; Haddad, Monoem (Frontiers in Physiology, 2018)
Objectives: The purpose of the study was to investigate performance, biomechanical, physiological, and psychophysiological effects of a simple and easily organized post-activation potentiation (PAP) re-warm-up performed before a 50-m freestyle swimming sprint. Methods: Regional level male adolescent swimmers [age: 13.0 ± 2.0 years; (min 11 years – max 15 years)] performed four trial conditions (three experimental, one control) on different days. The control trial involved a standardized 1200-m warm-up followed by 30 min of rest and a maximal 50-m freestyle swimming sprint. The experimental trials involved the same protocol but added a PAP component after a 20-min rest (10 min pre-50-m): The different PAP component involved the subjects in completing a 30-s maximal effort of: (1) push-ups (PU – upper body), (2) squats (SQ – lower body), and (3) burpees (BP – lower and upper body). Performance (time-trial), biomechanical (stroke length, stroke frequency), physiological (blood lactate concentrations, heart rate), and psychophysiological (ratings of perceived exertion) variables were collected. Results: The results demonstrated that the PAP protocols used in this investigation had no effect on swimming performance. Before the 50-m swimming sprint, the lactate values were significantly higher after the PU, BP, and SQ PAP loads compared to the control condition [P(CC-PU) = 0.02; P(CC-BP) = 0.01; P(CC-SQ) = 0.04]. For Lactate values, a significant and large effect of experimental condition compared to control condition was found (p < 0.05, η2 = 0.68). At 1 min after the 50-m time trial, significant differences were observed between the control condition and the different PAP loads [P(CC-PU) = 0.01; P(CC-BP) = 0.04; P(CC-SQ) = 0.01]. At 3 min after the 50-m sprint, significant differences were found between the control condition and the PU and SQ PAP loads [P(CC-PU) = 0.018; P(CC-SQ) = 0.008, respectively]. Additionally, a significant and large effect of experimental condition was found at 1 and 3 min after the 50-m swimming sprint (p < 0.05, η2(1 min) = 0.73; η2(3 min) = 0.59). There were medium sized but non-significant effects of interaction between the conditions, was illustrated for the mean HR values in response to the different conditions (p > 0.05; η2 = 0.083). Conclusion: None of the three PAP protocols showed any significant improvement in performance, biomechanical, physiological, and psychophysiological variables before, during and after the 50-m swimming time-trial. Further studies are warranted to investigate ways to improve swimming performance with simple body mass exercises performed in-between the end of pool warm-up and race start.